(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
Creating the conditions for competitive advantage in the world is the main condition for economic and social stability in Ukraine. Expected changes are possible only if the level of labor productivity, which in turn depends on the presence in the domestic labor market modern highly qualified specialists. Thus, any transformations in economy is impossible without reforming and modernizing training competitive specialists.